Impact of age at diagnosis on natural history of patients with elderly-onset ulcerative colitis: A French population-based study. Issue 9 (September 2018) - Duricova, Dana; Pariente, Benjamin; Sarter, Hélène; Fumery, Mathurin; Leroyer, Ariane; Charpentier, Cloe; Armengol-Debeir, Laura; Peyrin-Biroulet, Laurent; Savoye, Guillaume; Gower-Rousseau, Corinne; ,
Abstract: Background: Recent population-based study of elderly-onset Crohn's disease patients reported age-related differences in disease phenotype and outcome. Aims: The aim was to assess the impact of age at diagnosis on natural history of elderly-onset ulcerative colitis patients with emphasis on disease presentation, phenotype and treatment. Methods: Elderly-onset patients with ulcerative colitis (≥60 years at diagnosis) registered in a French population-based Registry EPIMAD (1988–2006) were included. Demographic and clinical data at diagnosis and at maximal follow-up were collected using predefined questionnaire. Results: Four-hundred and sixty-five elderly-onset ulcerative colitis patients were included (median follow-up 6.2 years); 276 (59%) were <70 and 189 (41%) ≥70 years at diagnosis. Patients aged <70 years presented with more rectal bleeding (86% vs. 79%, p = .06) and abdominal pain (44% vs. 34%, p = .04) while those ≥70 years had higher rate of left-sided colitis (62% vs. 49%; p = .02). Cumulative exposure to 5-ASA, corticosteroids and immunosuppressants was similar between the groups as well as surgery rate. However, patients <70 years were significantly more steroid-resistant than older individuals (12% vs. 3%, p < .05) while no significant difference in steroid-dependency was observed. Conclusion: Patients with elderly-onset ulcerative colitis differed in presentation, disease phenotype and response to medication with respect to age at diagnosis.